2019
DOI: 10.1101/671164
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A mesoderm-independent role for Nodal signaling in convergence & extension gastrulation movements

Abstract: 9During embryogenesis, the distinct morphogenetic cell behavior programs that shape tissues are influenced 10 both by the fate of cells and their position with respect to the embryonic axes, making embryonic patterning a 11 prerequisite for morphogenesis. These two essential processes must therefore be coordinated in space and 12 time to ensure proper development, but mechanisms by which patterning information is translated to the 13 cellular machinery that drives morphogenesis remain poorly understood. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…Furthermore, blocking Nodal receptor activity with SB505124 inhibits pescoid elongation ( Figure 4B). This is in line with recent work showing that Nodal signalling is important to drive convergence extension movements within animal caps [23].…”
supporting
confidence: 93%
“…Furthermore, blocking Nodal receptor activity with SB505124 inhibits pescoid elongation ( Figure 4B). This is in line with recent work showing that Nodal signalling is important to drive convergence extension movements within animal caps [23].…”
supporting
confidence: 93%
“…In zebrafish, opposing Nodal and BMP signaling gradients are thought to be necessary and sufficient for the establishment of the body plan as shown by experiments in which deployment of such gradients in animal caps leads to the formation of a complete anterior-posterior (AP) axis [ 14 ]. In addition to controlling cell fate assignments, a recent study has demonstrated that Nodal signaling is a key driver of convergence and extension movements and is sufficient to generate these behaviors when expressed within zebrafish animal caps [ 15 ]. Furthermore, BMP levels have been shown to be important for controlling cell movements during both gastrulation [ 16 ] and posterior body elongation [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…When large regions from the animal pole were taken, the remaining blastomere explant was defined as a small vegetal piece. Comparison of sizes by diameter at 5hpc were made using the Fiji line drawing tool and compared to similar explants at 1hpc in [ 3 ] and 2 somite stage [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, given the recent interest in studies of explanted tissues from zebrafish (e.g. (Williams and Solnica-Krezel, 2019;Xu et al, 2014), DIF-FRAC could also be readily applied to that powerful animal model.…”
Section: Discussionmentioning
confidence: 99%